Sectoral Aid Priorities: Missing MDG Targets? - Rainer Thiele; Peter Nunnenkamp; Axel Dreher (Poverty in Focus, 2007)
The prospects for achieving the Millennium Development Goals (MDGs) look bad in various developing countries, notably in Sub-Saharan Africa. To turn the tide, recent reports by the UN Millennium Project and the Commission for Africa issued urgent calls to increase official development aid substantially and, thereby, close the gap between donor rhetoric and reality. Qualitative aspects of aid allocation have received considerably less attention even though they may be as important for effectively meeting recipient needs. In particular, a needs-based targeting of aid in priority sectors such as health and education should have an important say on whether donors help achieving the MDGs. Hence, in addition to the usual ranking of donors according to their overall 'generosity', the structure of aid portfolios offers interesting insights as to whether aid has been prioritised in line with the MDGs. The sectoral composition of aid by all donors taken together has changed quite dramatically since the early 1990s. Most notable in the context of the MDGs, the share of aid devoted to the social sector has almost doubled (to about 35 per cent in 2002-04), with higher spending on education, health and population programs, though not on water and sanitation.
Keywords: 330; Developing Countries; Critique; Policymakers; Foreign Aid; Resource Allocation; Needs Assessment; Goals; UN; Administrative Personnel; Organization and Administration; Financial Activities; Economic Factors; Evaluation; Planning; International Agencies; Organizations; Political Factors; Sociocultural Factors